2023
DOI: 10.1186/s12915-022-01475-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screening reveals the genetic basis of mammalian embryonic eye development

Abstract: Background Microphthalmia, anophthalmia, and coloboma (MAC) spectrum disease encompasses a group of eye malformations which play a role in childhood visual impairment. Although the predominant cause of eye malformations is known to be heritable in nature, with 80% of cases displaying loss-of-function mutations in the ocular developmental genes OTX2 or SOX2, the genetic abnormalities underlying the remaining cases of MAC are incompletely understood. This study intended to identify the novel gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Among the reported stemness genes, our work showed that mRNA for PAX6 , BMI1 , SOX2 , and OCT4 genes were markedly reduced when CSSCs were expanded from P1 to P3. These downregulated genes are known to play roles in early ocular development and embryonic neural crest maintenance [ 31 ]. On the contrary, the more consistent expression of ABCG2 and NESTIN across P1 to P3 suggests that the expanded CSSCs attain certain levels of general stem cell characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported stemness genes, our work showed that mRNA for PAX6 , BMI1 , SOX2 , and OCT4 genes were markedly reduced when CSSCs were expanded from P1 to P3. These downregulated genes are known to play roles in early ocular development and embryonic neural crest maintenance [ 31 ]. On the contrary, the more consistent expression of ABCG2 and NESTIN across P1 to P3 suggests that the expanded CSSCs attain certain levels of general stem cell characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For each knockout (KO) line, abnormal phenotypes are being ascertained across a range of physiological systems through comparison with wild-type lines ( Kurbatova et al, 2015 ; Haselimashhadi et al, 2020 ). These gene–phenotype associations have been investigated to increase our knowledge on human disease using multiple, complementary approaches: (1) to learn about sexual dimorphism and pleiotropic traits ( Karp et al, 2017 ; Munoz-Fuentes et al, 2022 ), (2) to reveal previously unidentified candidate genes for multiple physiological systems and disease types ( Higgins et al, 2022 ; Bowl et al, 2017 ; Chee et al, 2023 ; Cacheiro et al, 2022 , 2020 ) and (3) to investigate how well the current phenotypic screens capture specific human traits ( Cacheiro et al, 2023 ; Lindovsky et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%